2021
DOI: 10.1111/1468-5973.12360
|View full text |Cite
|
Sign up to set email alerts
|

Cyber resilience during the COVID‐19 pandemic crisis: A case study

Abstract: The outbreak of the COVID‐19 pandemic crisis around the world and the resulting unprecedented measures taken by governments required organizations to quickly adopt new ways of (remotely) working. At face value, this would suggest a higher vulnerability for cyber threats. This research note analyses how a global financial institution dealt with this challenge by using Hollnagel's four abilities for resilient performance as a theoretical lens. Semi‐structured in‐depth interviews with eleven key actors were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Due to the overwhelming nature and scale of enterprises, the production output of many micro-enterprises has taken a significant hit, which has serious implications for national and global supply chains, businesses, and workers' livelihoods (Huang et al, 2020;Mayr et al, 2020;Qian et al, 2020). Even though MEs account for more than 90% of all businesses in Indonesia, the challenges they face will have an impact on the country's economic stability (Groenendaal & Helsloot, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the overwhelming nature and scale of enterprises, the production output of many micro-enterprises has taken a significant hit, which has serious implications for national and global supply chains, businesses, and workers' livelihoods (Huang et al, 2020;Mayr et al, 2020;Qian et al, 2020). Even though MEs account for more than 90% of all businesses in Indonesia, the challenges they face will have an impact on the country's economic stability (Groenendaal & Helsloot, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The government provides unprecedented and rapid assistance on a larger scale than it did following the 2008 financial crisis (Das et al, 2020). Tax breaks, direct loans, and grants to help with temporary layoffs, wage subsidies, and assistantships for working fewer hours are all available (Das et al, 2020;Groenendaal & Helsloot, 2021;Tran & Jeppesen, 2016). The logic behind these steps is "give money now, verify later," which is the correct approach; however, MEs must now recognize that in a changing world with increasingly sophisticated technological capabilities, digital transformation is the key to surviving current and future crises.…”
mentioning
confidence: 99%
“…The" online and remote life model" has become the new normal, whether society's progress, enterprise development, or way of life are rapidly moving forward digital development (Lee et al, 2021c;Zhang et al, 2021). The government is constantly summarizing experiences under the pandemic period, improving the emergency governance system and institutional mechanism construction, improving the resilience of urban governance (Groenendaal and Helsloot, 2021), and then achieving sustained and healthy economic development in the post-epidemic era. However, because the current digital maturity level in risk early warning and crisis response is not high, scientific and technological information technology applications have not landed in the market.…”
Section: The State Of the Artmentioning
confidence: 99%
“…The paper also proposed different methods for measuring cyber‐resilience, taking into account cyber‐security implementations as well as adversarial models. Still related to the analysis of cyber‐resilience, [ 104 ] analysed how a global financial institution (GFI) dealt with the cybersecurity challenges posed by COVID‐19. Authors conducted semi‐structured in‐depth interviews with 11 key actors from the GFI and leveraged Hollnagel's four abilities for resilient performance as a theoretical lens for their evaluation [ 105 ].…”
Section: Countermeasuresmentioning
confidence: 99%
“…The analysis however also showed that the favourable performance was obtained through many actions undertaken reactively rather than proactively, as it is instead advisable for a number of cybersecurity issues [ 106 ]. As such, [ 104 ] leaves open the question as to whether the four potentials should be developed beforehand, in order to perform resiliently during crises.…”
Section: Countermeasuresmentioning
confidence: 99%